Rotary ultrasonic-assisted abrasive flow finishing and its fundamental performance in Al6061 machining - Wang, Qiuyan (2022)
The geometric complexity of 3D-printed parts increases the difficulty of surface finishing with the conventional grinding technique. In this study, a rotary ultrasonic-assisted abrasive flow finishing (RUA-AFF) method is proposed towards improving the performance of the AFF process by providing rotary motion and ultrasonic vibration to the equipment. Finishing experiments are carried out involving Al6061 to investigate the capabilities of the proposed RUA-AFF. The obtained results show that (1) the higher ultrasonic vibration amplitude results in the greatest improvement in the work surface quality and a higher increase in material removal rate (MRR); (2) with the higher ultrasonic frequency and rotational speed, the surface roughness and MRR are decreased marginally; (3) there are two material remove modes in the RUA-AFF process: abrasive impingement and micro-cutting. These indicate that the high efficiency and high-quality finishing of Al6061 can be performed with the proposed RUA-AFF technique.